2020
DOI: 10.3390/ijerph17144980
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Healthcare Utilization among Chronic Obstructive Pulmonary Disease Patients with and without Cancer Receiving Palliative Care: A Population-Based Study in Taiwan

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic disease that burdens patients worldwide. This study aims to discover the burdens of health services among COPD patients who received palliative care (PC). Study subjects were identified as COPD patients with ICU and PC records between 2009 and 2013 in Taiwan’s National Health Insurance Research Database. The burdens of healthcare utilization were analyzed using logistic regression to estimate the difference between those with and without cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…34 A large Taiwanese study of PC involvement in patients with hepatic malignancy demonstrated a reduction in intenseive care unit and acute hospital admissions for patients supported by PC. 35 Our finding that the HepatoCare cohort experienced a reduction in hospital bed days is consistent with this and a recent US study found a substantial reduction in overall costs per patient with the integration of PC in this population. 36 Although assessing cost-effectiveness was not an objective of our study, these findings are certainly reassuring for health care providers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…34 A large Taiwanese study of PC involvement in patients with hepatic malignancy demonstrated a reduction in intenseive care unit and acute hospital admissions for patients supported by PC. 35 Our finding that the HepatoCare cohort experienced a reduction in hospital bed days is consistent with this and a recent US study found a substantial reduction in overall costs per patient with the integration of PC in this population. 36 Although assessing cost-effectiveness was not an objective of our study, these findings are certainly reassuring for health care providers.…”
Section: Discussionsupporting
confidence: 92%
“…ICU admission) in patients with advanced cirrhosis should make such patients ideal candidates for an integrated approach to supportive patient care 34 . A large Taiwanese study of PC involvement in patients with hepatic malignancy demonstrated a reduction in intenseive care unit and acute hospital admissions for patients supported by PC 35 . Our finding that the HepatoCare cohort experienced a reduction in hospital bed days is consistent with this and a recent US study found a substantial reduction in overall costs per patient with the integration of PC in this population 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic diseases have become an economic burden on health care worldwide [ 30 , 31 , 32 ]; patients present with mental and physical distress in their evolution [ 33 ] with chronic diseases such as cancer requiring long-term observation for decreased function and a greater episode of unpredictable acute care [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many family caregivers in Taiwan believe that artificial nutrition is essential to basic care; thus, they are reluctant to withdraw aggressive artificial nutrition even in the terminal stage. 25,[31][32][33] The gaps and disparities of resource utilization and life-sustaining support between palliative care and acute intensive care should be explored further in patients with glioblastoma.…”
Section: Physical Restraints and Artificial Nutritionmentioning
confidence: 99%